Estrogen Receptor α Signaling in Osteoblasts is Required for Mechanotransduction in Bone Fracture Healing - Steppe, Lena; Krüger, Benjamin Thilo; Tschaffon, Miriam Eva Angelica; Fischer, Verena; Tuckermann, Jan; Ignatius, Anita; Haffner-Luntzer, Melanie (Frontiers in Bioengineering and Biotechnology, 2021)
Biomechanical stimulation by whole-body low-magnitude high-frequency vibration (LMHFV) has demonstrated to provoke anabolic effects on bone metabolism in both non-osteoporotic and osteoporotic animals and humans. However, preclinical studies reported that vibration improved fracture healing and bone formation in osteoporotic, ovariectomized (OVX) mice representing an estrogen-deficient hormonal status, but impaired bone regeneration in skeletally healthy non-OVX mice. These effects were abolished in general estrogen receptor α (ERα)-knockout (KO) mice. However, it remains to be elucidated which cell types in the fracture callus are targeted by LMHFV during bone healing. To answer this question, we generated osteoblast lineage-specific ERα-KO mice that were subjected to ovariectomy, femur osteotomy and subsequent vibration. We found that the ERα specifically on osteoblastic lineage cells facilitated the vibration-induced effects on fracture healing, because in osteoblast lineage-specific ERα-KO (ERαfl/fl; Runx2Cre) mice the negative effects in non-OVX mice were abolished, whereas the positive effects of vibration in OVX mice were reversed. To gain greater mechanistic insights, the influence of vibration on murine and human osteogenic cells was investigated in vitro by whole genome array analysis and qPCR. The results suggested that particularly canonical WNT and Cox2/PGE2 signaling is involved in the mechanotransduction of LMHFV under estrogen-deficient conditions. In conclusion, our study demonstrates a critical role of the osteoblast lineage-specific ERα in LMHFV-induced effects on fracture healing and provides further insights into the molecular mechanism behind these effects.